Tertiary lymphoid structures: exploring opportunities to improve immunotherapy in ovarian cancer - Varghese, Aaron; Hess, Suzanne M.; Chilakapati, Shanmuga; Conejo-Garcia, Jose R.; McGray, A.J. Robert; Zsiros, Emese (Frontiers in Immunology, 2025)
Tertiary lymphoid structures (TLS) are organized ectopic lymphoid clusters of immune cells that develop in non-lymphoid tissue to promote antigen presentation, drive cytotoxic immune responses, and enhance humoral immunity via B cell clonal expansion. Their presence within the tumor microenvironment (TME) correlates with increased patient survival and an improved response to immune checkpoint inhibitors (ICIs), positioning TLS as potential predictive and prognostic biomarkers. Despite the widespread use of ICIs across various cancers, their effectiveness remains limited in gynecological malignancies, including ovarian cancer (OC), a notably challenging disease characterized by poor responses to both single and combination ICI therapies. Interestingly, the infiltration of T cells into the OC TME is linked to enhanced progression-free survival (PFS) and overall survival (OS), yet an immunosuppressive TME frequently impedes therapeutic efficacy, suggesting cell activity within localized immune niches can impact antitumor immunity. This review explores the roles of TLS, their maturity, functionality, identification, and related gene signatures; specific immune cells and cytokines that play a role in TLS formation and antitumor response; and other modifiable elements, including gut microbiota, that may drive improving OC survival by leveraging a TLS-driven antitumor response to bolster immunotherapy outcomes.